Developmental Dioxin Exposure Alters the Methylome of Adult Male Zebrafish Gonads - Akemann, Camille; Meyer, Danielle N.; Gurdziel, Katherine; Baker, Tracie R. (Frontiers in Genetics, 2019)
2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a persistent environmental toxicant and endocrine disrupting compound with reproductive and developmental effects in humans and model organisms, including zebrafish. Our previous microarray and histological studies found defects in spermatogenesis and fertility of zebrafish in response to acute developmental TCDD exposure. These effects are apparent following exposure during reproductive development, modeling fetal basis of adult-onset disease. Some outcomes of these previous studies (reduced fertility, changes in sex ratio, transcriptomic alterations) are also transgenerational - persisting to unexposed generations - through the male germline. We hypothesized that DNA methylation could be a possible mechanism for these reproductive effects and performed whole genome bisulfite sequencing (WGBS), which identifies whole genome DNA methylation status at the base pair level, on testes of adult zebrafish exposed to TCDD (two separate hour-long exposures to 50 pg/mL TCDD at 3 and 7 weeks post fertilization). In response to TCDD exposure, multiple genes were differentially methylated; many of which are involved in reproductive processes or epigenetic modifications, suggesting a role of DNA methylation in later-life health outcomes. Additionally, several ¬differentially methylated genes corresponded with gene expression changes identified in TCDD-exposed zebrafish testes, indicating a potential link between DNA methylation and gene expression. Ingenuity pathway analysis of WGBS and microarray data revealed genes involved in reproductive processes and development, RNA regulation, the cell cycle, and cellular morphology and development. We conclude that site-specific changes in DNA methylation of adult zebrafish testes occur in response to acute developmental TCDD exposure.